Love for sale: materialist readings of the troubadour razo corpus - Burgwinkle, William E. (New York London Garland Publishing, 1997)
This volume offers a polemical reading of a large and important body of troubadour songs featuring a double-pronged cultural studies approach: reading the texts through the filter of contemporary 13th-century commentary (the razos) and grounding the popularisation, canonisation, and influence of the troubadour phenomenon in issues of patronage, negotiations of power, and a developing market economy. The study is informed by recent work in feminist theory, queer studies, and new historical criticism, and asks questions that were usually skirted in more idealistic readings. As troubadour themes, melodies, and language moved beyond the borders of southern France, the songs were copied and collected in valuable manuscripts that conferred on them the status of "cultural capital." Uc de Saint Circ's arrival in Italy in the 1220s was a crucial moment in the elaboration of a genre of lyric poetry that is still prevalent in western culture. The troubadour that emerges from these readings is manipulative and self-fashioning, and his Lady is as often a symbol of power and patronage as a flesh-and-blood woman.The conflation of the male and the female, the masochistic and the opportunistic, the economic and the erotic, puts these texts at the very centre of contemporary concern with gender, subjectivity, and textuality.
A razo (Old Occitan: [raˈzu], literally "cause", "reason") was a short piece of Occitan prose detailing the circumstances of a troubadour composition. A razo normally introduced an individual poem, acting as a prose preface and explanation; it might, however, share some of the characteristics of a vida (a biography of a troubadour, describing his origins, his loves, and his works) and the boundary between the two genres was never sharp.
Keywords: Middle Ages (500-1400); Troubadour; Poetry; Music philosophy and esthetics; Cultural history; Music history; Biography; Literature; France; Occitanie (France)